Assessing the role of trichloroacetyl-containing compounds in the natural formation of chloroform using stable carbon isotopes analysis - Breider, F; Albers, C.N; Hunkeler, Daniel (Elsevier, 2013)
Chloroform (CHCl3) is an environmental contaminant widely distributed around world, as well as a natural compound formed in various aquatic and terrestrial environments. However, the chemical mechanisms leading to the natural formation of chloroform in soils are not completely understood. To assess the role of trichloroacetyl-containing compound (TCAc) in the natural formation of chloroform in forest soils, carbon stable isotope analyses of chloroform and TCAc in field samples and chlorination experiments were carried out. The isotope analysis of field samples have revealed that the δ13C value of natural chloroform (δ13Cmean = -25.8‰) is in the same range as the natural organic matter (δ13Cmean = -27.7‰), whereas trichloromethyl groups of TCAc are much more enriched in 13C (δ13Cmean = -9.8‰). A similar relationship was also observed for TCAc and chloroform produced by chlorination of natural organic matter with NaOCl. The strong depletion of 13C in chloroform relative to TCAc can be explained by carbon isotope fractionation during TCAc hydrolysis. As shown using a mathematical model, when steady state between formation of TCAc and hydrolysis is reached, the isotope ratio of chloroform is expected to correspond to isotope composition of NOM while TCAc should be enriched in 13C by about 18.3‰, which is in good agreement with field observations. Hence this study suggests that TCAc are likely precursors of chloroform and at the same time explains why natural chloroform has a similar isotope composition as NOM despite large carbon isotope fractionation during its release.
Keywords: Chloroform; Trichloroacetyl group; Isotope; Hydrolysis; Natural organic matter; Chlorination